2020
DOI: 10.3390/ijms21186495
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Interactions between Bile Acids and Plant Compounds—A Review

Abstract: Plant compounds are described to interact with bile acids during small intestinal digestion. This review will summarise mechanisms of interaction between bile acids and plant compounds, challenges in in vivo and in vitro analyses, and possible consequences on health. The main mechanisms of interaction assume that increased viscosity during digestion results in reduced micellar mobility of bile acids, or that bile acids and plant compounds are associated or complexed at the molecular level. Increasing viscosity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 123 publications
3
43
0
1
Order By: Relevance
“…Studies have shown that dietary fiber can protect against CG formation in prairie dogs, and this effect was associated with a decrease in the cholesterol level in bile ( Schwesinger et al, 1999 ). Reduced reabsorption of BAs in the ileum is considered a major mechanism that explains the cholesterol-reducing effects of dietary fibers ( Naumann et al, 2020 ). Several studies have reported that the viscous and adsorptive effects of dietary fibers can reduce BA reabsorption in the intestine ( Naumann et al, 2018 ; Naumann et al, 2019 ; Naumann et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that dietary fiber can protect against CG formation in prairie dogs, and this effect was associated with a decrease in the cholesterol level in bile ( Schwesinger et al, 1999 ). Reduced reabsorption of BAs in the ileum is considered a major mechanism that explains the cholesterol-reducing effects of dietary fibers ( Naumann et al, 2020 ). Several studies have reported that the viscous and adsorptive effects of dietary fibers can reduce BA reabsorption in the intestine ( Naumann et al, 2018 ; Naumann et al, 2019 ; Naumann et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced reabsorption of BAs in the ileum is considered a major mechanism that explains the cholesterol-reducing effects of dietary fibers ( Naumann et al, 2020 ). Several studies have reported that the viscous and adsorptive effects of dietary fibers can reduce BA reabsorption in the intestine ( Naumann et al, 2018 ; Naumann et al, 2019 ; Naumann et al, 2020 ). In the intestine, BAs are absorbed in two ways: active and passive ( Ticho et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, we found that an SV of B. wexlerae mediated the effect of red wine drinking on the CA dehydroxylation/deconjugation ratio, reflecting the conversion of glycine- or taurine-conjugated CA to unconjugated DCA within one cycle of the enterohepatic circulation. Red wine is rich in polyphenols, a group of molecules with anti-oxidative properties (Naumann et al, 2020; Queipo-Ortuño et al, 2012) that can increase fecal BA excretion by regulating gut microbiota (Chambers et al, 2019). We also observed that the frequency of chocolate consumption increases the GUDCA proportion in plasma through an SV of B. wexlerae .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, SLC and ABC transporters are expressed on the sinusoidal membrane and canalicular membrane of hepatocytes, thereby facilitating the uptake of drugs into hepatocytes and their excretion through the bile duct [ 19 ]. Bile excretion into the duodenum of the intestine can play a key role in the elimination of drugs through feces and drug reabsorption into the intestinal membrane, called enterohepatic circulation [ 28 ]. A schematic diagram of the position of various transporters in the hepatocytes is depicted in Figure 2 .…”
Section: Physiological and Biopharmaceutical Factors In The Brainmentioning
confidence: 99%